Chilling out : the cultural politics of substance consumption, youth and drug policy - Blackman, Shane J. (Open University Press, 2004)
Annotation "This text for sociology and applied social science courses argues for an holistic understanding of drugs in society, which can be a basis for a more coherent approach to drug control."--Jacket